Pengelolaan Limbah Medis, Non Medis, dan Benda Tajam di Rumah Sakit Rembang - Intan Sekar Arumdani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
The increasing number of hospitals has resulted in an increase in waste produced. Waste from health care facilities has the potential to spread disease if not properly processed. Hospital waste is included in the category of hazardous and toxic medical waste whose procedures and technical requirements for management are specifically regulated. The purpose of this study was to analyze the accuracy of solid B3 medical waste management at Rembang Hospital, including the stages of reduction, sorting, storage, and transportation. This study was a quantitative descriptive study. Data were obtained from observations, interviews and document reviews. The amount of medical waste produced was around 50 kg per day. The results of the analysis showed that the accuracy of medical waste management at Rembang Hospital was 71.69%. The percentage of compliance can be said to be still low and does not meet the requirements set by the government. Requirements that were not yet in accordance include the trolley used in the transportation process was not closed, there was no special route for transporting medical waste, temporary storage placed that do not meet standards, and there was a discrepancy in the use of personal protective equipment. Furthermore, it was concluded that medical waste management at Rembang Hospital is not in accordance with government regulations, so efforts are needed to improve the quality of management in the future.Keywords: hospital; medical waste; management ABSTRAK Peningkatan jumlah rumah sakit mengakibatkan bertambahnya limbah yang dihasilkan. Limbah yang berasal dari fasilitas pelayanan kesehatan berpotensi dalam penyebaran penyakit jika tidak diolah dengan tepat. Limbah rumah sakit masuk dalam kategori limbah medis bahan berbahaya dan beracun yang tata cara dan persyaratan teknis pengelolaannya diatur secara khusus. Tujuan penelitian ini adalah menganalisis ketepatan pengelolaan limbah medis padat B3 di Rumah Sakit Rembang, meliputi tahap pengurangan, pemilahan, penyimpanan, dan pengangkutan. Penelitian ini merupakan penelitian deskriptif kuantitatif. Data diperoleh dari pengamatan, wawancara dan telaah dokumen. Jumlah limbah medis yang dihasilkan adalah sekitar 50 kg per hari. Hasil analisis menunjukkan bahwa ketepatan pengelolaan limbah medis di Rumah Sakit Rembang adalah 71,69%. Persentase kesesuaian tersebut dapat dikatakan masih rendah dan belum memenuhi persyaratan yang diatur oleh pemerintah. Persyaratan yang belum sesuai meliputi troli yang digunakan dalam proses pengangkutan tidak tertutup, belum terdapat jalur khusus untuk mengangkut limbah medis, tempat penyimpanan sementara yang belum memenuhi standar, dan terdapat ketidaksesuain dalam penggunaan alat pelindung diri. Selanjutnya disimpulkan bahwa pengelolaan limbah medis di Rumah Sakit Rembang belum sesuai dengan regulasi pemerintah, sehingga diperlukan upaya peningkatan kualitas pengelolaan ke depan.Kata kunci: rumah sakit; limbah medis; pengelolaan